P144 Motor cortical stimulation versus voluntary relaxation to study muscle relaxation properties in different muscle conditions. Issue 3 (March 2017) - Molenaar, J.; Doorduin, J.; Voermans, N.; van Engelen, B.; Stegeman, D.
Abstract : Question: Transcranial magnetic stimulation (TMS) over the motor cortex can induce abrupt muscle relaxation by inhibition of corticospinal drive to the activated muscles. Voluntary relaxation (VR) is more commonly used to study muscle relaxation properties. These two methods have never directly been compared. The aim of our study is to investigate if variability of TMS-induced relaxation is lower compared to VR. To further validate the use of TMS in assessing muscle relaxation we studied the effects of cooling and fatigue to see if we could reproduce the well-known slowing effects of these conditions on muscle relaxation. Methods: Twenty-five subjects (14 men, 11 women) participated in this study. Handgrip dynamometry was used to assess relaxation properties of extrinsic finger flexors. Subjects performed repeated maximal voluntary contractions with VR and TMS-induced relaxation in fresh, cooled, and fatigued muscle conditions (Fig. 1). Peak relaxation rate (pRR), pRR normalized to maximal force (NpRR), and relaxation times were calculated. Within- and between-subject variability was assessed by calculating within- and between-subject coefficient of variability (CV), intraclass correlation coefficient (ICC), and repeatability coefficient (RC). Results: All outcome measures showed lower variability in TMS-induced relaxation compared to VR. This is demonstrated by lower within- and between-subject CV, ICC, and RC; e.g. for NpRR in men, TMS-induced relaxation has a within-subject CV of 3.3% vs 22.2% in VR, RC of 1.3 vs 6.1 s −1, ICC of 0.95 vs 0.60, and between-subject CV of 15.2% vs 27.4%.The slowing effects of cooling and fatigue could reliably be demonstrated using TMS (Fig. 2). Conclusions: Variability of TMS-induced muscle relaxation was lower compared to VR. A clinical implication is that for future studies on muscle relaxation, measurements are more reliable and less subjects would be needed using TMS to demonstrate differences in relaxation properties.